Outcomes research in chiropractic: the state of the art and recommendations for the chiropractic research agenda. - Nyiendo J; Haas M; Hondras MA (Journal of Manipulative & Physiological Therapeutics)
OBJECTIVE: To examine and document the state of the art in outcomes research in chiropractic, including the limitations of available data, and to make recommendations for further progress in this area. METHODOLOGY: An extensive search of the literature from 1990 through 1994 was undertaken using electronic databases (Medline, Index to Chiropractic Literature, EMBASE, and ERIC) and hand searches were conducted for relevant studies published in 1995. Publication in English, publication in a peer-reviewed journal, weight of evidence (study design) and measurement of patient-relevant outcomes were primary inclusion criteria. We prepared a draft with recommendation, rationale, actions required, responsible parties and expected outcomes for each seed statement. An outcomes workgroup, convened at the Research Agenda Work shop, added its perspective to the seed recommendations and actions required. Finally, the white paper authors prepared the final recommendations for outcomes research in chiropractic. RESULTS: This white paper presents six recommendations, emphasizing four general areas in which to develop the outcomes research agenda in chiropractic: research culture, infrastructure, opportunities and topics in outcomes research. CONCLUSION: The long-term goals of the chiropractic research agenda must be to advance the profession and to better meet the health needs of the public. Our final recommendations serve as a foundation for the development of proposals for future strategy with outcomes research a priority.